PENGARUH SKEPTISISME PROFESIONAL, KOMITMEN ORGANISASI, TEKANAN ANGGARAN WAKTU DAN KINERJA AUDITOR TERHADAP PERILAKU DISFUNGSIONAL AUDIT DENGAN EMOTIONAL SPIRITUAL QUOTIENT SEBAGAI VARIBEL MODERATING (Studi Empiris pada Inspektorat Provinsi Riau) - Nelda Pratiwi; Amir Hasan; Andreas Andreas (PEKBIS, 2019)
This study aimed to determine the effect of professional skepticism, organizationalcommitment, time budget pressure and the performance auditor on dysfunctionalaudit behavior with emotional spiritual quotient as a moderating variable. The studywas conducted in Inspectorate of Riau Province.The population is around theinternal auditor in the Inspectorate of Riau province, amounting to 88 respondents.The sampling data of this study using census sampling technique in which allmembers of the population used as sampel. Data collection techniques in this studyis in the form of a questionnaire,while the data analysis technique used is multipleregression analysis and moderate regression analysis and processed with SPSSversion 21 for windows. Partial regression test (t test) showed that professionalskepticism, organizational commitment, time budget pressure has influence ondysfunctional audit behavior and the performance auditor hasn’t influence ondysfunctional audit behavior. Moderate regression analysis showed that professionalskepticism, organizational commitment, and time budget pressure on dysfunctionalaudit behavior moderated by emotional spiritual quotient has influence ondysfunctional audit behavior, except the performance auditor.